Stakeholders’ Opinion Regarding Design of Agricultural Insurance in Punjab - Zada, Ahmad Mubasher Wahab; Mohapatra, Lopamudra; Anand, Anupam (Indian Journal of Extension Education, 2021)
Agricultural insurance is one of the mechanisms to stabilize and protect the farm economy. Agricultural Insurance schemes such as Pradhan Mantri Fasal Bima YojanaÂ (PMFBY) aim to improve the productivity and earnings of farmers while Weather Based Crop InsuranceÂ Scheme (WBCIS) aims to mitigate the hardship of the insured farmers against the likelihood of financial loss on account of anticipated crop loss resulting from adverse weather conditions. There was a significant difference in opinion of scientists and extensionists regarding the coverage of food crops, insurance unit,s and coverage of losses under PMFBY. The focus of appropriating the index is to minimize the basis risk i.e. for PMFBY the insurance unit is affixed as the village panchayat, coverage of post-harvest losses and trigger yield, whereas for the WBCIS it is the density of weather station, coverage of parametric weather exigencies and correlation between weather index and yield of the crop. In case of WBCIS, both the scientists and extensionists significantly differed in their opinion regarding coverage of crops since; these were less risky crops for farmers of Punjab. The insurance product planned for Punjab state needs to be designed based on strong agronomic principles